2013
DOI: 10.1093/cercor/bht319
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Zones Selective to Faces and Written Words in the Human Ventral Occipitotemporal Cortex

Abstract: Recognition of faces and written words is associated with category-specific brain activation in the ventral occipitotemporal cortex (vOT). However, topological and functional relationships between face-selective and word-selective vOT regions remain unclear. In this study, we collected data from patients with intractable epilepsy who underwent high-density recording of surface field potentials in the vOT. "Faces" and "letterstrings" induced outstanding category-selective responses among the 24 visual categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…Notably, regions demonstrating word-selectivity are clustered around the intersection of the occipito-temporal sulcus (OTS) and the anterior MFS ( Fig 6 ), consistent with prior studies of word selectivity that have localized cortical regions sensitive to orthographic stimuli to the general vicinity of the OTS (i.e. the visual word-form area) [ 13 , 17 , 45 , 76 78 , 112 , 127 ]. Given that word, tool, animate, and face stimuli are typically dependent on central vision [ 23 , 43 , 44 , 46 ], the co-localization of word-selectivity with these other categories remains consistent with our original prediction that word-selectivity should be observed in regions with foveal bias.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, regions demonstrating word-selectivity are clustered around the intersection of the occipito-temporal sulcus (OTS) and the anterior MFS ( Fig 6 ), consistent with prior studies of word selectivity that have localized cortical regions sensitive to orthographic stimuli to the general vicinity of the OTS (i.e. the visual word-form area) [ 13 , 17 , 45 , 76 78 , 112 , 127 ]. Given that word, tool, animate, and face stimuli are typically dependent on central vision [ 23 , 43 , 44 , 46 ], the co-localization of word-selectivity with these other categories remains consistent with our original prediction that word-selectivity should be observed in regions with foveal bias.…”
Section: Discussionsupporting
confidence: 85%
“…Because 5 categories in all were evaluated, for each category j , N will be equal to 4. In this fashion, each electrode could be judged selective for multiple categories [ 112 ].…”
Section: Methodsmentioning
confidence: 99%
“…), and the converse pattern holds true for faces. A similar pattern was observed in a recent study using high‐density recording of surface field potentials in the ventral occipitotemporal cortex of patients with intractable epilepsy, revealing striking within‐hemisphere interdigitation of face‐ and letter‐string–selective zones . Together, these findings undermine the argument for strict lateralization of face and word representations.…”
Section: Hemispheric Specialization Is Gradedsupporting
confidence: 80%
“…Decoding the phase patterns in theta and alpha oscillations provided relatively higher discrimination accuracy than did the delta, beta and gamma band oscillations. Previous studies suggested that the ventral occipital-temporal (vOT) cortex is involved in the perception of visually presented objects and written words (Dahaene, 1995 ; Price and Devlin, 2011 ; Matsuo et al, 2015 ). Our decoding analysis showed a higher classification power for electrodes placed in occipital-temporal regions compared to other regions, although we should keep in mind that EEG electrodes do not necessarily pick up activity directly under the electrodes.…”
Section: Discussionmentioning
confidence: 99%